2019
DOI: 10.1002/anie.201900703
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Multi‐Conformational Control Through Deformable Carbon‐Sulfur Bond for Singlet‐Triplet Emissive Tuning

Abstract: Crystal‐state luminophores have been of great interest in optoelectronics for years, whereas the excited state regulation at the crystal level is still restricted by the lack of control ways. We report that the singlet‐triplet emissive property can be profoundly regulated by crystal conformational distortions. Employing fluoro‐substituted tetrakis(arylthio)benzene luminophores as prototype, we found that couples of molecular conformations formed during different crystallizations. The deformable carbon‐sulphur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 60 publications
1
64
0
1
Order By: Relevance
“…As well-known, different molecular conformations could result in different molecular packing modes, and then further influence their corresponding properties [29,[31][32][33][34][35][36][37][38]. Phenothiazine derivatives with quasi-axial (ax) and quasi-equatorial (eq) conformations show distinct features due to the different electronic configurations caused by the existence of d orbitals from sulfur atom [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…As well-known, different molecular conformations could result in different molecular packing modes, and then further influence their corresponding properties [29,[31][32][33][34][35][36][37][38]. Phenothiazine derivatives with quasi-axial (ax) and quasi-equatorial (eq) conformations show distinct features due to the different electronic configurations caused by the existence of d orbitals from sulfur atom [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the extent of substitution can be ordered by careful control of the reagents nucleophilicity and the reaction conditions and is summarized in Figure 1. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In general, there are few approaches reported to selectively afford mono-substitution of HFB, while disubstitution is generally obtained under mild conditions at room temperature. Stronger bases, longer reaction times, higher temperatures and a greater concentration of thiols can orient the reaction toward tetrasubstitution while hexa-substitution can be achieved with even harsher conditions and a larger excess of thiols.…”
mentioning
confidence: 99%
“…[6] To date,many investigations on the relationship between UOP behavior and molecular packing have been reported. [7] It was revealed that the molecular packing style in the solid state usually plays avital role in tailoring the UOP lifetime, [8] emission efficiency, [9] luminescent color, [10] and even realizing the unique dynamic UOP and mechanoinduced persistent phosphorescence emission. [11] Despite great success in studying the relationship between the phosphorescence properties and molecular packing modes,the underlying mechanism for the UOP is still unclear, owing to the complex factors that influence phosphorescence.T herefore,adeeper understanding of the effective molecular packing is of great importance.…”
mentioning
confidence: 99%